THE MEANING OF THE SIDDIQ VALUE IN FINANCIAL ACCOUNTABILITY AT THE UNIVERSITY OF MUSLIM NUSANTARA (UMN) AL WASHLIYAH MEDAN - Yurmaini Yurmaini; Khairil Anshari (Green Publisher, 2022)
Ideally, Islamic organizations including educational institutions such as the Muslim Nusantara University (UMN) Al Washliyah Medan have implemented Islamic values, one of the Islamic values that should flow in the veins is the value of siddiq (honesty) including in carrying out financial activities so that financial accountability able to increase public trust in it. In reality, there are still many Islamic Higher Education Institutions that have not made the value of siddiq as the basis for financial management and have not received public trust that Islamic Higher Education Institutions will act honestly in carrying out economic activities. The purpose of this study is to find out how the meaning ( interpretation and implementation ) of the value of Siddiq in financial accountability at UMN Al Washliyah Medan . This research is a qualitative research with a phenomenological approach and an interpretive paradigm. The data collection method is interview Vice Chancellor II and Head of Finance UMN Al Washliyah Medan , observation and documentation. Data analysis techniques are data collection, data reduction and drawing conclusions. Techniques for guaranteeing the validity of the data are credibility test, transferability, dependability, comfirmability , and the NVivo 12 Plus program . The results of this study concluded that the shiddiq value at UMN was interpreted as being right, planning and using it according to what was intended, true meaning in harmony between what was said and what was done in terms of use and financial reporting. The implementation of the shiddiq value is carried out in 3 (three) ways, namely shiddiq in financial planning, financial management, and financial reporting.